Purple Biodeterioration in Parchment: a Case in the Alcobacense Collection - Pinheiro, C (2025)
The understanding of purple biodeterioration, or the appearance of purple tinged stains in parchment, has seen a sharp evolution in the last few years. Modern molecular analysis of the DNA, using Next-Generation Sequencing, have made it possible to hypothesize a chain of events triggered by the presence of Archaeobacteria in the parchment, a succession theory that builds on the presence of complex biological communities to explain the appearance of such stains. A few of the codices in the Alcobacense collection display such a disease – termed measles – and this paper tells of the results obtained after the analysis performed on one of them, Alcobacense 338.